2013
DOI: 10.1021/ma4000682
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Confined Crystallization of Polyethylene Nanophases in Epoxy Thermosets

Abstract: In this contribution, we reported the investigation of the formation and confined crystallization behavior of polyethylene nanophases in epoxy thermosets. The nanostructured epoxy thermosets were prepared by the use of a poly(ε-caprolactone)-block-polyethylene-block-poly(ε-caprolactone) (PCL-b-PE-b-PCL) triblock copolymer. The crystalline midblock (viz. PE) of the triblock copolymer was prepared from an α,ω-diacetoxy-terminated polycyclooctadiene with the molecular weight as high as M n = 11,000, which was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…The results of both DSC and DMTA indicated that the PCL chains grafted onto the surfaces of the BT NPs were miscible with the epoxy matrices. The miscibility of the PCL chains with epoxy networks was attributed to the formation of intermolecular hydrogen‐bonding interactions between the carbonyl groups of the PCL chains and the hydroxyl groups of the epoxy networks …”
Section: Resultsmentioning
confidence: 95%
“…The results of both DSC and DMTA indicated that the PCL chains grafted onto the surfaces of the BT NPs were miscible with the epoxy matrices. The miscibility of the PCL chains with epoxy networks was attributed to the formation of intermolecular hydrogen‐bonding interactions between the carbonyl groups of the PCL chains and the hydroxyl groups of the epoxy networks …”
Section: Resultsmentioning
confidence: 95%
“…The nanophases are not formed until the curing reaction occurs with the sufficiently high conversion of the precursors. In the past decade, there have been a great number of reports on the preparation of the nanostructured thermosets by using a variety of block copolymers via self-assembly or RIMPS approach [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is realized that thermosets can be significantly toughened via the formation of the nanostructures; the mechanisms of toughness improvement are attributable to the debonding of micelles (or vesicles) from thermosetting matrix, crack deflection or frictional interlocking in the thermosets displaying the terraced morphology [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Wide angle (WA) XRD showed that the formation of PE nanophases didn't alter the structure of the crystals (72). 652 Feldman EP/MMT prepared through solid state reaction was melt-processed with PA6.…”
Section: Thermoplastic-thermoset Polymer Blend Nanocompositesmentioning
confidence: 99%